Using Harter and Likert Response Formats in Middle Childhood: A Comparison of Attachment Measures. (December 2020) - Marci, Tatiana; Moscardino, Ughetta; Lionetti, Francesca; Santona, Alessandra; Altoé, Gianmarco
Self-report questionnaires based on Harter's response format ("Some kids . . . but other kids . . . ") are commonly used in developmental and clinical research settings, but the reliability and validity of this format in middle childhood are still under debate. The current study aimed to test the psychometric proprieties of Harter versus Likert response formats as applied to two attachment questionnaires in a sample of 410 Italian children aged 8 to 10 years. Participants completed the Experiences in Close Relationships–Revised Child version ( n = 102, 4-point Likert-type scale; n = 104, adapted Harter version) and the Security Scale ( n = 95, Harter's format; n = 109 adapted 4-point Likert version). Results of multigroup confirmatory factor analyses indicated that the two response formats exhibited comparable reliability and factorial validity, although a slight superiority of Harter's format emerged for the Security Scale. External validity was supported for both answer formats. Implications for developmental theory and practice are discussed.